2019
DOI: 10.1186/s43031-019-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling competence in science education

Abstract: Research on the understanding of the nature of models and modeling processes in science education have received a lot of attention in science education. In this article, we make five claims about the research on modeling competence in science education. The five claims are (1) the development of modeling competence in practice is essential to scientific literacy for twenty-first century citizens, (2) further research is needed to build a holistic and theoretical understanding of models and modeling knowledge (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 63 publications
2
32
0
6
Order By: Relevance
“…They claimed, in line with previous studies (Aktan, 2016;Torres & Vasconcelos, 2017;Yenilmez Turkoglu & Oztekin, 2016), that the use of models in school would make science more exciting and enjoyable and would involve pupils directly in the teaching and increase their urge to further explore. This experience supports Oh and Oh's (2011) suggestions that cyclic modelling can improve teaching practices and that modelling-based scaffolding frameworks can enhance engagement in scientific practice (Chiu & Lin, 2019).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…They claimed, in line with previous studies (Aktan, 2016;Torres & Vasconcelos, 2017;Yenilmez Turkoglu & Oztekin, 2016), that the use of models in school would make science more exciting and enjoyable and would involve pupils directly in the teaching and increase their urge to further explore. This experience supports Oh and Oh's (2011) suggestions that cyclic modelling can improve teaching practices and that modelling-based scaffolding frameworks can enhance engagement in scientific practice (Chiu & Lin, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…Being exposed to different modelling-based activities made the PSTs consider how they might include such activities in a classroom with pupils, which is important for all science teachers (Oh & Oh, 2011). As developing modelling competence is essential to scientific literacy for 21st-century citizens (Chiu & Lin, 2019) and is part of modern science education (NDET, 2019;OECD, 2019), modelling practices must be included in teacher education to make teaching more process-oriented (Nielsen & Nielsen, 2019;Oh & Oh, 2011). Olufsen et al (2017) found that PSTs who were educated with an emphasis on the connection between subject knowledge, education strategies and practice included teaching…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Someone who has scientific literacy is willing to engage in reasoning discourse on science and technology. It requires competence explains scientific phenomena so that they recognize, offers and evaluates explana-tions for various natural and technological phenomena; evaluating and designing scientific research to describe and assess scientific investigations, and to propose ways of handling scientific questions; and interpreting data and scientific evidence to analyze and evaluate data, claims, and arguments in various representations and draw appropriate scientific conclusions (Chiu & Lin, 2019). All competencies also require students' abilities in terms of collaborating, communicating, thinking critically, and evaluative.…”
Section: Science Competencymentioning
confidence: 99%